(untitled) (Italiano LinguaDue, 2025)
L’allestimento dell’edizione moderna dell’Anticrusca di Paolo Beni è stato l’occasione di collazionare alcuni esemplari dell’editio princeps del 1612 al fine di valutare l’opportunità di condurre un’indagine più approfondita ed estesa, seguendo i criteri della textual bibliography. L’articolo descrive i risultati di questa collazione esplorativa, che ha messo in luce l’esistenza di due tipi di varianti di stati: varianti di stato minori, che non influiscono sulla trasmissione del testo; varianti più significative, che coinvolgono intere pagine e che sono la testimonianza dell’intento dell’autore di migliorare il testo a livello argomentativo. Sarà così possibile valutare con maggior cognizione di causa l’opportunità o meno di approfondire ulteriormente l’indagine. About a modern edition of Paolo Beni’s Anticrusca: an investigation of state variants in the 1612 editio princeps The preparation of the modern edition of Paolo Beni’s Anticrusca provided an opportunity to collate a number of copies from the 1612 editio princeps in order to assess the advisability of conducting a more thorough and extensive investigation, following the criteria of textual bibliography. The article describes the results of this exploratory collation, which revealed the existence of two types of state variants: minor state variants, which do not affect the transmission of the text; more significant variants, which involve entire pages and are evidence of the author’s intent to improve the text at the argumentative level. It will then be possible to make a more informed assessment of whether or not further investigation is appropriate.